Flow behaviors and dynamic recrystallization mechanisms study of TC4 under different temperatures and strain rates - Duqiang Ren; Chuanyong Chen; Haijun Xuan; Huimin Zhou; Guo Li (Journal of Materials Research and Technology)
The flow behavior of TC4 was studied through thermal compression experiments conducted at deformation temperatures of 910, 930, 950, and 970 °C, and strain rates of 0.01, 0.1, 1, and 10 s−1. After hot deformation, the dynamic recrystallization mechanisms were characterized by electron backscattered diffraction (EBSD) technology. The results showed that the flow stress increased with rising strain rate and decreased with increasing temperature. A constitutive equation, based on the Zener-Holloman parameter, was constructed to predict the flow stress. The resulting model accurately predicted the flow stresses of TC4, with a relative mean prediction error of 7.9%. Analysis of EBSD results revealed that three recrystallization mechanisms coexisted in the current experimental study. Discontinuous dynamic recrystallization was identified as the dominant mechanism, complemented by geometric dynamic recrystallization, and followed by continuous dynamic recrystallization. A relatively small grain size, averaging 4.08 μm, can be obtained at a deformation temperature of 930 °C. Additionally, the trend in grain size variation was comparatively stable at a strain rate of 0.1 s⁻1, with an average grain size of 4.21 μm.